(untitled) (Research, Society and Development, 2024)
Acute Pancreatitis (AP) is an inflammatory syndrome of the pancreas that can vary significantly in terms of severity, from mild and self-limited forms to severe quadros with risk of fatal complications. This condition can be triggered by various factors, such as gallstones, excessive alcohol consumption, trauma, infections and use of medications. The present article aims to address a physiopathological line of PA in a clinical context. This study is a narrative review with the purpose of discussing and discovering the pathophysiology of PA in its clinical context. The data bank was used: SciElo (Scientific Electronic Library Online) and PubMed (US National Library of Medicine), with language restrictions (Portuguese) and giving priority to articles published between 2000 and 2022. A PA is a clinical condition with manifestations varied, ranging from mild forms to serious and potentially fatal symptoms. Early identification of patients with a risk of evolution for severe forms continues to be a challenge, once the diagnosis often occurs in advanced stages. The management of BP requires a multidisciplinary approach, involving fluid ressuscitation, sleep control, early nutrition and appropriate interventions, such as the use of antibiotics or endoscopic and surgical procedures, depending on the pregnancy of the quadro.